KOMPATIBILITAS EKSTRAK Piper retrofractrum Vahl. DAN Curcuma xanthorrhiza Roxb. UNTUK PENGENDALIAN Helopeltis antonii Sign. - NFN Rohimatun; NFN Dadang; I Wayan Winasa; Sri Yuliani (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Plant extracts as a botanical insecticide can be used in either single or mixture forms. Mixed extracts have advantages: reducing dependence on one plant species, being the synergistic effect which can increase the effectiveness of formulas, and reducing the possibility of resistance emergence. This study aimed to obtain compatible and synergistic comparisons of P. retrofractum with C. xanthorrhiza extracts that effectively control the third instar nymph of Helopeltis antonii. The comparison of P. retrofractum and C. xanthorrhiza extracts were 4:1, 2:1, 1:1, 1:2, and 1:4 (w/w). The experiment was performed in a completely randomized design using the contact method. The LC50, LC90, and LC95 values were calculated using the PoloPlus Ver 1.0 Program. The mixture interaction was determined from the Combination Index value. The results showed that P. retrofractum extract was compatible and synergistic with C. xanthorrhiza extract at a ratio of 2:1 (w/w). These were the best combination shown by the lowest LC50, LC90, and LC95 values and showed consistently strong synergistic properties compared to other concentrations. The components of P. retrofractum may be responsible for the insecticidal properties are piperine; piperanine; piperidine; 3,4-Pyridinedimethanol,6-methyl; Piperidine,1-[5-(1,3-benzodioxol-5-yl)-1-oxo-2,4-pentadienyl]-,(Z,Z)-; and (2E,4E,12E)-1-(Piperidine-1-yl)octadeca-2,4,12—trien-1-one. The insecticidal activity of C. xanthorrhiza may associated with its content of xanthorrhizol, Ar-curcumene, β-curcumene, curzerene, germacrone, 7-zingiberene, caryophyllene, and β-bisabolol. A combination of these two plant extracts has the potential to be further developed as a botanical insecticide to control H. antonii.